Swedish-Finnish glossary: Moomin characters - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary containing Moomin character names. Published in Kieliviesti 3/1999. Contains 26 entries. 1999.

Svensk-sverigefinsk ordlista med muminfigurernas namn. Publicerades i Kieliviesti 3/1999. Innehåller 26 ord. 1999.
Svensk-finsk ordlista: muminfigurer
Keywords: literature; litteratur; Juvenile Literature; Barn- och ungdomslitteratur [Publikationstyp]; literature; litteratur; literature; litteratur; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik